Hawking Non-thermal and Purely Thermal Radiations of Rotating Black Hole in Anti-de Sitter Space Time by Hamilton-Jacobi Method - Hossain, M Ilias (GANIT: Journal of Bangladesh Mathematical Society, 2018)
We have explored Hawking non-thermal and purely thermal radiations of Kerr-anti-de Sitter (KAdS) black hole using massive particles tunneling method by taking into account the space time background as dynamical, energy and angular momentum as conserved incorporating the selfgravitation effect of the emitted particles. The results we have obtained for KAdS black hole have shown that the tunneling rates are related to the change of Bekenstein-Hawking entropy and the derived emission spectrum deviates from the pure thermal spectrum and also the obtaining results for KAdS black hole are accordant with Parikh and Wilczek’s opinion and gives a correction to the Hawking radiation of KAdS black hole. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 99-109